Molecular and functional imaging for detection of lymph node metastases in prostate cancer - Fortuin, Ansje S.; Rooij, Maarten de; Zamecnik, Patrik; Haberkorn, Uwe; Barentsz, Jelle O. (International journal of molecular sciences, 2013)
Knowledge on lymph node metastases is crucial for the prognosis and treatment of prostate cancer patients. Conventional anatomic imaging often fails to differentiate benign from metastatic lymph nodes. Pelvic lymph node dissection is an invasive technique and underestimates the extent of lymph node metastases. Therefore, there is a need for more accurate non-invasive diagnostic techniques. Molecular and functional imaging has been subject of research for the last decades, in this respect. Therefore, in this article the value of imaging techniques to detect lymph node metastases is reviewed. These techniques include scintigraphy, sentinel node imaging, positron emission tomography/computed tomography (PET/CT), diffusion weighted magnetic resonance imaging (DWI MRI) and magnetic resonance lymphography (MRL). Knowledge on pathway and size of lymph node metastases has increased with molecular and functional imaging. Furthermore, improved detection and localization of lymph node metastases will enable (focal) treatment of the positive nodes only.
Gesehen am 26.04.2021